Determination of Spatial and Temporal Changes in Surface Water Quality of Filyos River (Turkey) Using Principal Component Analysis and Cluster Analysis - YAĞANOĞLU, Elif; YAĞANOĞLU, Aycan Mutlu; ARSLAN, Gokhan; SÖNMEZ, Adem Yavuz (Marine Science and Technology Bulletin, 2020)
Monitoring water quality is one of the high priorities for the protection of water resources. Many different approaches are used to analyse and interpret the variables that determine the variance of water quality observed in various sources. Statistical methods, especially multivariate statistical techniques, constitute an important part of these approaches. In this study, ten water quality parameters, which were measured for twelve months from seven stations determined on Filyos River, were evaluated by carrying out principal component analysis (PCA) and cluster analysis (CA) from multivariate statistical methods. In addition, dominant quality parameters designating the quality of the water source were determined. According to PCA results, 4 principal components contained the key variables and accounted for 69.49% of total variance of surface water quality from Filyos River. Dominant water quality parameters were observed to be temperature, EC, DO and pH. While the study revealed that the river is exposed to agricultural pollution alongside with the water quality character generated by the climatic conditions, it also suggested that multivariate statistical methods are useful tools in evaluating complex data sets such as water quality data, and monitoring the quality of water resources.
Keywords: principal component analysis; Naval architecture. Shipbuilding. Marine engineering; SH1-691; VM1-989; Limnology; Aquaculture. Fisheries. Angling; Ziraat Mühendisliği (Diğer); Naval Science; Limnoloji; Agricultural Engineering (Other); V; Çevre Bilimleri; Filyos River; Surface water quality; Principal component analysis; Cluster analysis; filyos river; Water Resources and Water Structures; Environmental Sciences; surface water quality; Su Kaynakları ve Su Yapıları; cluster analysis; 14. Life underwater; 15. Life on land; 6. Clean water; 13. Climate action